DRUG LIKENESS SCORING AND STRUCTURE ACTIVITY/PROPERTY RELATIONSHIPS OF 1,2,3-TRIAZOLE DERIVATEVES AS AROMATASE INHIBITOR - Ouassaf, M; Belaidi, s; Belaidi, H; Almi, Z (university of el oued/جامعة الوادي, 2018)
Molecular geometry, electronic structure and effect of the substitution for 1,2,3-triazole derivatives, have been studied by molecular mechanics, ab initio/HF and DFT /B3LYP. The molecular electrostatic potential surface (MESP) which displays the activity centers of a molecule and the substitution effects on its systems have been performed by HSAB (Hard Soft Acid and Base) principle application. Also, the structure-activity/property relationship studies were applied on twenty-two molecules of 1, 2, 3-triazole derivatives, all have the aromatase inhibitory activity. Results such as net charges, bond length, dipole moment, QSAR p op L p k ’ pa a a L pop l Eff y (L pE) a po pap .
Article
Keywords: 1,2,3-triazole; MESP; SAR; Drug likeness; aromatase